Fatigue-related symptom clusters and functional status of older adults in hospice. Issue 1 (February 2023) - Abduljawad, Suzan F.; Beckstead, Jason W.; Dobbs, Debra; Visovsky, Constance; Rodriguez, Carmen S.; McMillan, Susan C.; Wang, Hsiao Lan
Abstract: Background: Fatigue is frequently co-existing with other symptoms and is highly prevalent among patients with cancer and geriatric population. There was a lack of knowledge that focus on fatigue clusters in older adults with cancer in hospice care. Objectives: To identify fatigue-related symptom clusters in older adult hospice patients and discover to what extent fatigue-related symptom clusters predict functional status while controlling for depression. Method: This was a cross-sectional study in a sample of 519 older adult hospice patients with cancer, who completed the Memorial Symptom Assessment Scale, the Center for Epidemiological Studies Depression, Boston Short Form Scale, and the Palliative Performance Scale. Data from a multi-center symptom trial were extracted for this secondary analysis using exploratory factor analysis and hierarchical multiple regression analysis. Results: Data from 519 patients (78 ± 7 years) with terminal cancer who received hospice care under home healthcare services revealed that 39% of the participants experienced fatigue-related symptom clusters (lack of energy, feeling drowsy, and lack of appetite). The fatigue cluster was significantly associated positively with depression ( r = 0.253, p < 0.01), and negatively with functional status ( r = −0.117, p < 0.01) and was a strong predictor of participants' low functional status. Furthermore, depression made a significant contribution to this predictive relationship. Conclusion: Older adult hospice patients with cancer experienced various concurrent symptoms. The fatigue-specific symptom cluster was identified significantly associated with depression and predicted functional status. Fatigue should be routinely monitored in older adults, especially among hospice cancer patients, to help reduce psychological distress and prevent functional decline.